2019
DOI: 10.1515/jpm-2019-0103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal obesity on pregnancy outcomes in women delivering singleton babies: a historical cohort study

Abstract: Background Obesity in pregnancy is increasing worldwide, reaching epidemic proportions in many countries and frequently creating challenges for obstetricians. We conducted this study to assess the effects of maternal obesity on maternal and perinatal outcomes. Methods A historical cohort study was performed on 16,609 women who delivered singleton babies in a 5-year period (2013–2017). Data were retrieved from the Cruces Perinatal Database (CPD) and only women whose prepregnancy body mass index (BMI) was known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
44
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 23 publications
11
44
0
8
Order By: Relevance
“…Among the main strengths of the study, the large sample size and the scarcity of studies focused on specific aspects of breastfeeding such as starting in the first hour or skin-to-skin contact can be highlighted. On the other hand, the prevalence of obesity in our study was similar to other studies, such as that by Parveen et al [2], who observed a prevalence of obesity of 31.6%, and the one by Melchor et al [32], with a prevalence of 18.4%. Because of this, we believe that our sample provides an adequate representation of women with high BMIs.…”
Section: Discussionsupporting
confidence: 92%
“…Among the main strengths of the study, the large sample size and the scarcity of studies focused on specific aspects of breastfeeding such as starting in the first hour or skin-to-skin contact can be highlighted. On the other hand, the prevalence of obesity in our study was similar to other studies, such as that by Parveen et al [2], who observed a prevalence of obesity of 31.6%, and the one by Melchor et al [32], with a prevalence of 18.4%. Because of this, we believe that our sample provides an adequate representation of women with high BMIs.…”
Section: Discussionsupporting
confidence: 92%
“…28 Various Indian and international studies depicting similar results were found. [29][30][31] Also, we found higher odds for preterm, macrosomia, IUFD and NICU admissions in study group. In a cohort study by Doi relation between high maternal BMI and pregnancy outcome was studied.…”
Section: Resultssupporting
confidence: 56%
“…33,34 Studies by Doi et al, Su et al, Castillejos et al, and Melchor et al also endorses similar results. 29,[30][31][32]35…”
Section: Resultsmentioning
confidence: 99%
“…Çalışma sonunda gebelerin %22,6'sının IOM'un önerdiği vücut ağırlığından daha azını, %50,0'ının ise önerilenden daha fazlasını kazandığı gözlenmiştir [3]. Fetal gelişimin devamlılığı ve sağlıklı bir doğum için önerilen vücut ağırlığı kazanımı sağlanmalıdır [4]. Ancak yapılan çalışmalarda hafif şişman ve/veya obez kadınlarda önerilenden daha az ağırlık kazanımının fetal gelişime olumsuz bir katkısının olmadığı gözlenmiştir.…”
Section: Tablo 1 Iom Ve Acog Prenatal Ağırlık Kazanımı öNerileri *Niunclassified
“…Ancak yapılan çalışmalarda hafif şişman ve/veya obez kadınlarda önerilenden daha az ağırlık kazanımının fetal gelişime olumsuz bir katkısının olmadığı gözlenmiştir. Bu sebeple hafif şişman/obez gebelerde önerilenden daha az ağırlık kazanmış ancak herhangi bir fetal sorun yaşanmamış ise gebeyi daha fazla ağırlık kazandırmaya yönlendirmek maternal ve fetal sonuçlar açısından bir iyileşme getirmeyeceği için gerekli değildir [4,5]. Ayrıca çalışma sonuçlarına göre IOM'un önerdiği değerlerin altında ağırlık kazanmış obez ve hafif şişman gebelerde maternal ve fetal herhangi bir komplikasyon gözlenmemiş, bebeklerin doğum ağırlıklarının normal sınırlarda olduğu saptanmıştır.…”
Section: Tablo 1 Iom Ve Acog Prenatal Ağırlık Kazanımı öNerileri *Niunclassified